Code Mixing in College Students’ Presentation: A Case in an Intercultural Communication Class - Jauhar Helmie; Halimah Halimah; Aan Hasanah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
Studying the second language (L2) was happens around the world because of some reasons such as education. Studying another language can be important in intellectual human activities after studying first language (L1). However using L2 is quite hard because some of them use L2 just for some their activities, not for the whole of their activities, such as students who use English only when studying English subject only or on the contrary. Nowadays, some people use two language at the same time, which is called code mixing. The use of two codes for communication can help them to make clear their explanation from another language that they used. The purpose of this research is concerning on the use of code mixing in college students’ presentation in Intercultural Communication class. Apart from that, there is an attempt to find out the language dominate in their presentation, the reasons of code mixing use in their presentation and the response of the audience about code mixing in presentation. The Method use is qualitative by using class presentation as the instrument, the writer collected the data of the college students’ presentation, questionnaire to the audience and interview to the presenters. The research findings showed that the languages dominate in the presentation are English language and Bahasa Indonesia equally. The reasons’ student in use code mixing is to make the explanation clear, and the response of the audience is 56.83% of the students give positive response in using code mixing of the presenter.